Perancangan Sistem Informasi Akuntansi Laporan Penghasilan Komprehensif Pengelolaan Air Warga Pada PT Saranamas Dinamikatama Berbasis Website Dengan Menggunakan PHP Dan Postgresql - Rahayu, Syifa Siti; Yulianto, Hery Dwi (@is The Best : Accounting Information Systems and Information Technology Business Enterprise, 2023)
The current management of community water businesses still uses a manual or conventional system. The conventional system that occurs is that the officer manually records the use of water made in a recap, and then the financial section has no accounting information system, so it still uses Google Spreadsheets and accounting processes that refer to the accounting standards designed. Based on existing problems, a website-based accounting information system for comprehensive income reports for citizen water management is needed. The research objective is to build a website-based Citizen Water Management Comprehensive Income Report Accounting Information System. The research method used was descriptive survey research, in which the author describes a situation or phenomenon systematically in a clear and detailed manner, including processes and components that occur, to find solutions to the problems found. The population in the study is the financial details of the water fund in 2022, and the sample is the financial details of the water report for October 2020. The types of data collection methods are interviews, observation, and library research. In research, the type of design used is descriptive analysis with primary data. One of the system methods is the waterfall method. The result of his research was the design of a comprehensive income reporting accounting information system for web-based community water management so that it facilitates the process of recording transactions and producing accurate financial reports for citizen water management.